Development and Characterization of Transfersomes for Improved Transdermal Administration of Ketoprofen (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Examining transfersomes as a potential transdermal delivery mechanism for the poorlysoluble medication was the objective of the current investigation. Ketoprofen, in order to getaround the problems with taking it orally. The rotational vacuum evaporation and sonicationprocess, along with a non-ionic surfactant (span 80) and phosphatidyl choline, were used to createseveral transfersomal formulations. The finished products were examined using a variety oftechniques, including light microscopy, particle size analysis, turbidity, drug content, rheology,surface charge and density, penetration ability, in vitro release, ex vivo permeation, skinirritation/sensitivity study, and stability studies. We used the paw edema test paradigm to seewhether the improved formulation had any anti-inflammatory effects on rats. The drug was foundto be compatible with the excipients in FTIR and DSC investigations. Findings showed that allformulations effectively captured Ketoprofen with consistent drug content. Because itdemonstrated the highest levels of drug entrapment (95.69±0.17%) and cumulative percent drugrelease (74.34±0.34), the optimal formulation (F4-S1-R4) was determined to be a transfersomalformulation consisting of 85% phosphatidyl choline of the medication and 15% span 80. Weevaluated the ex vivo permeation profiles of the various transfersomal formulations with F4-S1-R4. The F4-S1-R1 transfersomal formulation outperformed the F4-S1-R2, F4-S1-R3, F4-S1-R4,and F4-S1-R5 in terms of cumulative drug permeation and flux, as well as lag time (p